Thermal erosion of metal surfaces under the action of fine-focused scanning electron beams; Journal of Engineering Physics and Thermophysics; Vol. 20, № 2 - Bleykher (Bleicher) G. A. Galina Alekseevna (2011, 2011)
Title screen